The Role Of Earnings Volatility In Singapore And Malaysia - Tiong, Angela Ee Ling (Universiti Malaysia Sarawak (UNIMAS), 2014)
Singapore Stock Exchange (SGX) is historically been considerably more volatile than the Bursa Malaysia (BM). This is somewhat surprising given the many similarities of the two markets. The mainly difference between the two market is that trading volume is substantially higher in Singapore because Singapore is more technology information compare with Malaysia. The study investigates the role of earnings volatility in Malaysia and Singapore. Yearly data used in this study which covers period ranging from 2003 to 2012. The methodology used in the study is descriptive statistics, pearson correlation coefficient and multiple regression analysis. Based on the previous study, Singapore stock experienced extremely large price movement than Malaysia, thus, Singapore stock prices may have deviated from their basic values. The findings show that the Singapore is more volatile than Malaysia.